Application of Analytical Hierarchy Method in Selection of Raw Material Suppliers at PT Integrated Services Claims - Setiawan, Endra; Irwansyah, Irwansyah (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
Raw material prices are an important concern for companies in creating cost efficiencies. Price is one of the purchasing considerations, prices that are too low make buyers doubt the quality of goods to make purchases and vice versa, prices that are too expensive make buyers switch to other vendors. PT. Klaai Integrated Services is a company engaged in the catering industry that serves several large companies in Bekasi Regency such as PT. Unilever Indonesia, PT. Astra Honda Motor, PT. Suzuki Indomobil Motor, PT. Kalbe Farma, Tbk, PT. Yasulor Indonesia and others. PT. Integrated Services Claims are very selective in vendor selection. The high frequency of changing vendors every month was allegedly influenced by price differences between several vendors, so the company took the initiative to switch to vendors with more competitive prices. This study aims to determine the priority order of criteria and suppliers to be selected for purchasing raw materials at PT Klaai Jasa Terkomunikasi. This research is a descriptive research with the method approach used, namely descriptive qualitative and quantitative research. Data collection was carried out by observing, interviewing and distributing questionnaires by means of data analysis using the AHP approach. The results of this study indicate that the most influential criteria in the selection of wood suppliers at PT Klaai Jasa TerIntegrated are quality criteria with a weight of 0.486, while for the second priority, namely price criteria with a weight of 0.371, and delivery accuracy is the third priority with a weight of 0.143.